Physiologic Adaptations to Modifying Resistive Load and Time Under Tension During Expiratory Muscle Strength Training. - Dakin, Avery E.; Rau, Sydney; Villarreal-Cavazos, Katya; Easterly, Kelly; Huber, Jessica E.; Garber, Carol Ewing; Quinn, Lori; Hegland, Karen W.; Troche, Michelle S. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: The purpose of this study was to test the impact of modifying resistive load and time under tension (TUT) on respiratory excursion, submental excitation, and ratings of perceived exertion/effort (RPE) during expiratory muscle strength training (EMST). Task specificity between EMST, cough, and swallowing was also explored. Method: Participants were outfitted with respiratory bands, submental surface electromyography, and a microphone. Tasks included maximal expiratory pressure (MEP) testing, voluntary and reflex cough testing, cup sips, and EMST. EMST included three sets of 10 repetitions in four conditions: short (0.2 s) at 50% MEP, long (1 s) at 50% MEP, short at 75% MEP, and long at 75% MEP (L75). Outcomes were respiratory kinematics, cough airflow, submental excitation, and RPE. Multilevel models and pairwise comparisons were used for statistical analysis. Results: Twenty healthy adults (M = 27 ± 5 years) participated. There were significant effects between EMST conditions where rib cage excursion ranged from 5% to 24% (of maximum), abdominal excursion ranged from 6% to 19%, submental excitation ranged from 40% to 57%, and RPE varied (p < .05). Several pairwise contrasts during cough and swallowing showed no significant differences with EMST conditions. Submental excitation during L75 was higher than the swallowing condition (p = .03). Conclusions: Exercise parameters including resistive load and TUT that impacted the acute physiologic responses to EMST should be considered during exercise prescription to maximize physiologic adaptations and training specificity. Future research will examine the longitudinal impacts of modifying EMST exercise parameters on coughing and swallowing outcomes.